Relevansi Fiqih Klasik terhadap Fenomena Wanita Karir sebagai Pemimpin di Era Modern serta Batasan Kepemimpinan Wanita Karir Menurut Al-Qur’an, Hadis, dan Ijtihad Para Ulama - Sri Mulyani Nursamsiah; Tina Risdiyanti; Rival Fauzi (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The increasing involvement of women in the workforce and various strategic leadership positions is a growing phenomenon in modern society. This reality has given rise to various studies on the role of women as career women and leaders from an Islamic perspective. This situation arises from differences in interpretation between classical and contemporary Islamic jurisprudence regarding women's leadership. Classical scholars generally place certain limitations on women's leadership, while contemporary thinkers tend to emphasize aspects of competence, usefulness, and social conditions as the basis for assessing a person's suitability for leadership. This study aims to analyze the concept of career women, the Islamic perspective on women's professional activities, and women's leadership roles within the family and community. The method used is library research with a descriptive-analytical approach through a review of various Islamic sources and relevant academic literature. The results show that Islam, in principle, provides opportunities for women to participate in the workplace and public life as long as they adhere to sharia values ​​and fulfill their responsibilities within the family. Furthermore, the understanding of women's leadership is evolving; in the contemporary context, leadership legitimacy is determined more by capacity, integrity, trustworthiness, and social contributions than by gender. Keywords: Career Women, Women's Leadership, Classical Fiqh, Contemporary Fiqh, Islamic Perspective